Analisis Faktor yang Memengaruhi Loyalitas Pasien di Rumah Sakit Umum Daerah - Hasibuan, Reza Rahmadi; Hasanah, Yulia Nur; Dewi, Rustina; Purwatiningsih, Purwatiningsih (Jurnal Manajemen Bisnis dan Keuangan, 2023)
The purpose of this study was to analyze the factors that influence patient satisfaction and loyalty in regional public hospitals. This study used a survey with 235 participants and used Structural Equation Modeling (SEM) to get the research results. The results show that the patient is not at all affected by the service quality of RSUD Dr. M. Ashari Pemalang. The happiness of patients at RSUD Dr. M. Ashari Pemalang was influenced by their estimate of hospital prices. The positive corporate image of RSUD Dr. M. Ashari Pemalang is useful for patients in making decisions. RSUD Dr. M. Ashari Pemalang does not care about improving the quality of his services because his patients remain loyal. The impression of a price that benefits patients at RSUD Dr. M. Ashari Pemalang has a direct impact on practice retention rates. There is a positive relationship between the image of RS Dr. M. Ashari Pemalang with patient retention.